Postpartum depression in adolescent mothers - Katharine J. Dinwiddie; Tracy L. Schillerstrom; Jason E. Schillerstrom (Taylor & Francis Group, 2018)
Background: Postpartum depression has been extensively studied in adults but is less understood in adolescent mothers, despite a prevalence that is double that observed in adult mothers. The purpose of this review was to describe the epidemiology, risk factors, treatment and prognosis for adolescents with postpartum depression. We also sought to identify limitations of the available literature and propose areas for future study targeting postpartum depression in this vulnerable population. Methods: A Medline literature search was conducted for articles published between 1996 and 2015. We identified relevant studies by combining the indexed search terms 'pregnancy in adolescence or teenage pregnancy' and 'depression or postpartum depression'. Additional studies were identified from references of selected articles. We limited our search results to adolescents (18 years or younger) and English language publications. Case studies/series and editorials were excluded. Results: The Medline database search identified 134 articles of which 57 met inclusion criteria. Ten additional articles were identified from reference lists yielding a total of n = 67 articles for review. Among the articles selected, 10 described epidemiology, 27 identified risk factors, nine measured long-term outcome and 21 proposed treatment strategies for postpartum depression in adolescent mothers. Conclusions: There is limited literature addressing adolescent postpartum depression, but there has been a significant growth of interest in recent years. There is a need for more randomized control trials to establish gold standards for assessing postpartum depression in adolescent mothers and standards for treatment in these patients.